Stereoselective Biginelli-like reaction catalyzed by a chiral phosphoric acid bearing two hydroxy groups - Hu, Xiaoyun; Guo, Jianxin; Wang, Cui; Zhang, Rui; Borovkov, Victor (Beilstein Journal of Organic Chemistry, 2020)
To develop new efficient stereoselective catalysts for Biginelli-like reactions, a chiral phosphoric acid bearing two hydroxy groups derived from ʟ-tartaric acid was successfully synthesized via highly regioselective transformations of enantiopure 1,1,4,4-tetraphenylbutanetetraol. The obtained catalyst effectively catalyzed Biginelli-like reactions with moderate to good enantioselectivities. Control experiments indicated that the presence of the two hydroxy groups were indispensable for achieving a high enantioselectivity.
Keywords: asymmetric Biginelli-like reaction; chiral 1,1,4,4-tetraphenylbutanetetraol; chiral phosphoric acid

(untitled) - Matos, L. H. S.; Masson, F. T.; Simeoni, L. A.; Homem-de-Mello, M. (Eur. J. Med. Chem., 2018)

(untitled) - Kaur, R.; Chaudhary, S.; Kumar, K.; Gupta, M. K.; Rawal, R. K. (Eur. J. Med. Chem., 2017)

(untitled) - Nagarajaiah, H.; Mukhopadhyay, A.; Moorthy, J. N. (Tetrahedron Lett., 2016)

(untitled) - Cho, H. (Heterocycles, 2013)

(untitled) - Kappe, C. O.; Stadler, A. (Org. React., 2004)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Gong, L.-Z.; Chen, X.-H.; Xu, X.-Y. (Chem. – Eur. J., 2007)

Multicomponent Reactions - Kappe, C. O. (The Biginelli reaction, 2005)

(untitled) - DeBonis, S.; Simorre, J.-P.; Crevel, I.; Lebeau, L.; Skoufias, D. A.; Blangy, A.; Ebel, C.; Gans, P.; Cross, R.; Hackney, D. D.; Wade, R. H.; Kozielski, F. (Biochemistry, 2003)

(untitled) - Biginelli, P. (Gazz. Chim. Ital., 1893)

(untitled) - Munoz-Muniz, O.; Juaristi, E. (ARKIVOC, 2003)

(untitled) - Huang, Y.; Yang, F.; Zhu, C. (J. Am. Chem. Soc., 2005)

(untitled) - Chen, X.-H.; Xu, X.-Y.; Liu, H.; Cun, L.-F.; Gong, L.-Z. (J. Am. Chem. Soc., 2006)

(untitled) - Li, N.; Chen, X.-H.; Song, J.; Luo, S.-W.; Fan, W.; Gong, L.-Z. (J. Am. Chem. Soc., 2009)

Catalysts for Fine Chemical Synthesis - Rueping, M.; Sugiono, E.; Azap, C.; Theissmann, T. (Metal-Free Reduction of Imines: Enantioselective Brønsted Acid-Catalysed Transfer Hydrogenation using Chiral BINOL-Phosphates as Catalysts, 2007)
The synthesis has been described as part of the synthesis of the corresponding phosphoric acid derivative.

(untitled) - Akiyama, T.; Saitoh, Y.; Morita, H.; Fuchibe, K. (Adv. Synth. Catal., 2005)

(untitled) - Hu, X.; Zhang, R.; Xie, J.; Zhou, Z.; Shan, Z. (Tetrahedron: Asymmetry, 2017)

(untitled) - Shan, Z.; Hu, X.; Zhou, Y.; Peng, X.; Li, Z. (Helv. Chim. Acta, 2010)

(untitled) - Hu, X.; Shan, Z.; Peng, X.; Li, Z. (Tetrahedron: Asymmetry, 2009)

(untitled) - Hu, X.; Shan, Z.; Song, S. (Tetrahedron: Asymmetry, 2014)

(untitled) - Hu, X.; Shan, Z.; Soloshonok, V. A. (Cryst. Growth Des., 2012)

(untitled) - Hu, X. Y.; Yin, Z. Y.; Tang, Y. L.; Wu, L. M. (J. South-Cent. Univ. Natl., Nat. Sci. Ed., 2019)

(untitled) - Li, S.; Lü, J.; Luo, S. (Acta Chim. Sin. (Chin. Ed.), 2018)

(untitled) - Győrffy, N.; Tungler, A. (J. Mol. Catal. A: Chem., 2011)

(untitled) - Han, J.; Soloshonok, V. A.; Klika, K. D.; Drabowicz, J.; Wzorek, A. (Chem. Soc. Rev., 2018)

(untitled) - Han, J.; Kitagawa, O.; Wzorek, A.; Klika, K. D.; Soloshonok, V. A. (Chem. Sci., 2018)

(untitled) - Soloshonok, V. A.; Wzorek, A.; Klika, K. D. (Tetrahedron: Asymmetry, 2017)

(untitled) - Hosaka, T.; Imai, T.; Wzorek, A.; Marcinkowska, M.; Kolbus, A.; Kitagawa, O.; Soloshonok, V. A.; Klika, K. D. (Amino Acids, 2019)

(untitled) - Han, J.; Wzorek, A.; Kwiatkowska, M.; Soloshonok, V. A.; Klika, K. D. (Amino Acids, 2019)